Contribuições para a caracterização da paisagem minerária: Mina Córrego do Meio - June Elaine Minomi (2020)
This dissertation defines landscape as a fragment of the territory, which conforms and changes spatially according to the dynamics from environmental, economic and socio-cultural relationships. This research aims to understand how to characterize the mining landscape through an interdisciplinary and holistic approach, with the purpose of contributing for new use of mined areas and in landscape management as well. To achieve this objective, methodologies on the landscape were interpreted; potential existing gaps were verified in the territorial planning and management instruments related to the mined areas; and the fundamentals of practices for new uses of these areas were identified. This theoretical basis allowed a greater understanding of the concept of landscape character and mined areas, making it possible to list the main aspects considered in the characterization of the mining landscape. In this research, references that adopt methods based on theories of landscape planning were analyzed, including Design with Nature by Ian L. McHarg and Landscape Ecology by Richard T.T. Forman, as well as works based on the Landscape Character Assessment (LCA). Given the recognition of the importance of landscape from Quadrilátero Ferrífero, this research supports the hypothesis that the landscape characterization must be integrated to the process of elaborating new use of mined area, enabling its reintegration into the territory from an environmental, economic and socio-cultural perspective. It is expected that the result of this dissertation will contribute to the contemplation on the future of post-mined areas and, to a certain extent, may assist those involved in the mine closure process in the search for appropriate suggestions for these areas.